Neuroendocrine Characteristics Of Early Trauma And Its Relation To Bullying. (2017)
The aim of this article is to review the theoretical basis of neurobiological and neuroendocrine mechanisms that develop early trauma, which can be generators cognitive and emotional vulnerability in subjects exposed to environments with characteristics